2018
DOI: 10.1186/s12939-018-0722-3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing or treating malnutrition in homeless problem-drinkers: a systematic review

Abstract: BackgroundExcessive drinking leads to poor absorption of nutrients and homeless problem-drinkers often have nutritionally inadequate diets. Depletion of nutrients such as vitamin B1 can lead to cognitive impairment, which can hinder efforts to reduce drinking or engage with services. This review aimed to assess effectiveness of interventions designed to prevent or treat malnutrition in homeless problem-drinkers.MethodsWe systematically searched nine electronic databases and 13 grey literature sources for studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Interventions included education, supplementation (ie, intramuscular, oral tablet or fortified food product based), and provision of food products (ie, hot meals or food rations). Although multicomponent interventions lead to improved nutritional behaviour in some studies, results were not consistent across others . Therefore, holistic and individualised nutritional interventions post admission to hospital should be formulated by a trained nutritional professional, considering psychosocial aspects of care and long term follow up and evaluation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Interventions included education, supplementation (ie, intramuscular, oral tablet or fortified food product based), and provision of food products (ie, hot meals or food rations). Although multicomponent interventions lead to improved nutritional behaviour in some studies, results were not consistent across others . Therefore, holistic and individualised nutritional interventions post admission to hospital should be formulated by a trained nutritional professional, considering psychosocial aspects of care and long term follow up and evaluation.…”
Section: Discussionmentioning
confidence: 93%
“…There were no identified studies included in this review that focussed on addressing malnutrition despite the known nutritional risk of this patient population. A recent systematic literature review undertook a review of interventions for the prevention or treatment of malnutrition in homeless problem drinkers . Although participants were not recruited from a hospital inpatient admission for alcohol withdrawal, the outcomes reported in this review are relevant when considering nutritional intervention on discharge from acute hospital based care.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, recent studies on only 1 lifestyle factor, especially smoking, have shown effects among patients with alcohol and drug addiction, but here, the interventions seem to be longer, reaching up to 12 months for smoking [3]. Another important element could be handling out healthy food products [13]. The VIP study did not include similar interventions.…”
Section: Discussionmentioning
confidence: 95%
“…This information is an integrated part of the VIP. Few studies have been conducted on food interventions, but a review including a broad variety of study designs and qualities indicates that handing out food products to homeless problem drinkers seems to be effective [13]. Overall, an effect of mono-factor interventions and not the comprehensive VIP may add to some existing general experiences of taking 1 step at a time.…”
Section: Introductionmentioning
confidence: 99%
“…One is the decrease in thiamin absorption in the small intestine, which is already mentioned above. Another reason is that alcohol intake causes decreased caloric intake from sources other than alcohol and thus reduces the supply of thiamin from the diet . In addition, liver cirrhosis, a complication of chronic alcoholism, also leads to a decreased supply of thiamin to the liver .…”
Section: Risk Factors For Thiamin Deficiencymentioning
confidence: 99%